(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The article aims to systematize the structuring axes of theatrical pedagogy present in some of the groups that were part of the Nuestra America Cultural Workers Front, through texts by playwrights and directors and the experience of the groups. The aim is to identify common characteristics in organizational forms and resistance processes. To this end, the research recovers the history of the articulation of the workers of Culture in the 1960s and 1970s in Latin America. It analyzes the process of composition of the network that emerges inspired by the debates, actions and aesthetic proposals of that period, the Network of Political Theater Popular from Nuestra América.